(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the life, scholarly formation, major works, and enduring theological contribution of Imam Abu Mansur Muhammad al-Maturidi al-Samarqandi (d. 333 AH/944 CE), the founder of one of the two principal schools of Sunni Islamic theology. The study traces his intellectual lineage within the Hanafi jurisprudential tradition of Samar kand, surveys the content and significance of his two canonical works – Kitab alTawhid and Ta’wilat Ahl alSunna – and analyses his distinctive positions on the balance between reason and transmitted evidence, the divine attributes, the definition of faith (iman), the freedom of human action, and the relationship between major sin and the boundaries of belief. The article situates the Maturidiyya within the broader landscape of classical Islamic theology as the moderate school positioned between the rationalism of the Mu’tazila and the textualism of the Ash’ariyya, and concludes by reflecting on the contemporary relevance of Maturidi thought as a scholarly bulwark against dogmatic extremism.